(untitled) (Academia Journal of Medicine, 2019)
Background: Influenza is a seasonal infectious viral disease which accounts for approximately 3-5 million cases of severe illness and 250,000 to 500,000 deaths in a yearly outbreak. The objectives of our study were to study the various clinical presentation of influenza infection and to correlate the demographic data and clinical symptoms with hematological parameters. Subjects and Methods: 95 cases which were positive by One-step RT-PCR were included in the study. Elevation of serum transaminase levels, thrombocytopenia and raised creatinine levels are important parameters which mandates vigilant follow up in patients with influenza infection. Results: The most common symptoms were fever in 88.42% and cough in 88.42% of cases. 51.57% of patients presented with anemia on admission. 11.5% of patients had thrombocytopenia of which 36.36% had elevated liver enzymes. 35.78% of cases had leukocytosis of which 32.35% had elevated liver enzymes. 15.78% of patients had raised creatinine levels. Conclusion: Authors suggested that elevation of serum transaminase levels, thrombocytopenia and raised creatinine levels are important parameters which mandates vigilant follow up in patients with influenza infection.